2004
DOI: 10.1289/ehp.6684
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution and mortality in a cohort of Norwegian men.

Abstract: We investigated the association between total and cause-specific mortality and individual measures of long-term air pollution exposure in a cohort of Norwegian men followed from 1972-1973 through 1998. Data from a follow-up study on cardiovascular risk factors among 16,209 men 40-49 years of age living in Oslo, Norway, in 1972-1973 were linked with data from the Norwegian Death Register and with estimates of average yearly air pollution levels at the participants' home addresses from 1974 to 1998. Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
4
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(172 citation statements)
references
References 32 publications
10
147
4
10
Order By: Relevance
“…Similar to the multicity Canadian study, results from these studies also seem to implicate traffic-related air pollution components, as identified by NO 2 and soot (black smoke), which are sometimes more robustly associated with mortality than PM mass (Nafstad et al, 2004;Filleul et al, 2005). As spatial correlations among PM 2.5 , soot, and NO 2 are generally high, the observed results do not allow disentanglement of the role of these components in causing mortality effects following long-term exposure.…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 62%
“…Similar to the multicity Canadian study, results from these studies also seem to implicate traffic-related air pollution components, as identified by NO 2 and soot (black smoke), which are sometimes more robustly associated with mortality than PM mass (Nafstad et al, 2004;Filleul et al, 2005). As spatial correlations among PM 2.5 , soot, and NO 2 are generally high, the observed results do not allow disentanglement of the role of these components in causing mortality effects following long-term exposure.…”
Section: Surrogate Measures Of Pollutant Mixturesmentioning
confidence: 62%
“…One study from Oslo included 16,000 men, of whom 25% died during the follow up [103]. This cohort, with people 40–49 years of age at the start of the study, was followed from 1972/73 through 1998.…”
Section: Resultsmentioning
confidence: 99%
“…A related problem is that of comparing disparate measures of traffic exposure, such as effects of exposure to Pb (Menke et al, 2006;Schober et al, 2006), NO 2 (Nafstad et al, 2004), PM 10 (Burr et al, 2004), noise, or traffic proximity. An RR based on the mean value may be used to compare the effects of total removal of each of these agents, irrespective of how they were measured.…”
Section: Measures Of Effect (Risk)mentioning
confidence: 99%
“…Premature mortality (Roemer and van Wijnen, 2001;Hoek et al, 2002;Finkelstein et al, 2004;Nafstad et al, 2004;Lipfert et al, 2006a, b;Maynard et al, 2007). Increased hospitalization (Hagen et al, 2000;Janssen et al, 2002;von Klot et al, 2005;Wellenius et al, 2005;Lanki et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%